Laser phototherapy as a treatment for radiotherapy-induced oral mucositis - Lino,Maíra Dória Martinez da Costa (2011)
Oral mucositis is a harmful side effect of radiotherapy (RT) on the head and neck region. There are encouraging reports on the beneficial aspects of the use of laser light on the treatment of oral mucositis. This paper reports the efficacy of laser phototherapy (LPT) on the treatment of oral mucositis in a patient undergoing RT after surgical removal of a squamous cell carcinoma with osseous invasion of the maxilla. Palatal and commissural lesions were treated with λ660 nm, 40 mW, ∅=4 mm², in contact mode, 5 x 2.4 J/cm² per point, 14.4 J/cm² per session. For treating the lesion on the patient's nasal mucosa, LPT (∅=4 mm², λ780 nm, 70 mW, 3 x 2.1 J/cm² per point, 6.3 J/cm² per session, contact mode) was used on the external area of the nose. A single dose (2.4 J/cm²) with the λ660 nm laser, as described before, was applied on the entrance of each nostril. LPT was used 3 times/week during 4 weeks. Treatment results indicate that the use of LPT on oral mucositis was effective and allowed the patient to carry on the RT without interruption. However, long-term and controlled clinical trials are necessary to establish both preventive and curative protocols using LPT.